2007
DOI: 10.1016/j.ntt.2006.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced auditory acuity in rat pups from excess and deficient omega-3 fatty acid consumption by the mother

Abstract: Consumption of the nutrients omega-3 fatty acids (ω-3 FA) during pregnancy and lactation is considered beneficial to fetal and infant development. It may also reduce the incidence and severity of preterm births by prolonging gestational length. However several recent human and animal studies have reported that over-supplementation with ω-3 FA, especially in the form of fish oil, can have adverse effects on fetal and infant development and the auditory brainstem response (ABR). Our goal was to assess further th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 53 publications
1
47
0
1
Order By: Relevance
“…Because of limited financial resources and the principle of reducing animal usage [78], the CON group was borrowed from a concurrent study in our laboratory [16-18]. The CON group consisted of n=23 litters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of limited financial resources and the principle of reducing animal usage [78], the CON group was borrowed from a concurrent study in our laboratory [16-18]. The CON group consisted of n=23 litters.…”
Section: Methodsmentioning
confidence: 99%
“…Imbalances in the number of males and females within each litter were dictated by which offspring survived until the time of ABR testing. Pups were ABR-tested on PND 24 to simulate prior ABR developmental toxicology studies [16-18]. The rat ABR is well-developed by PND 24 [21].…”
Section: Methodsmentioning
confidence: 99%
“…Longer auditory conduction times, indicating slower conduction through the brainstem auditory pathway, can result from structural damage or delayed development [24] . We [25,26] and Church et al [27] previously reported that auditory brainstem conduction times were significantly longer in the offspring of rats fed high levels of DHA or fish oil during pregnancy and lactation. Since conduction time is strongly associated with the degree of myelination of fibers within the auditory tracts [28] , the negative effects of high levels of dietary DHA on auditory brainstem responses may be mediated through effects on myelin.…”
Section: Introductionmentioning
confidence: 55%
“…The higher levels of maternal dietary DHA were associated with longer auditory brainstem conduction times [25,26] , and with later postnatal appearance of the auditory startle reflex [25,33] . Church et al [27] also reported that auditory brainstem conduction times were significantly longer in offspring of dams fed diets high in n3 fatty acids. These studies suggest that high levels of maternal DHA during pregnancy and/or lactation may exert negative effects on central neural system development, potentially through effects on myelin.…”
Section: Discussionmentioning
confidence: 95%
“…Des effets négatifs ont aussi été observés chez le rat en cas d'excès d'apport d'omégas 3 avec une altération de l'acuité auditive ainsi qu'un infléchissement de la croissance postnatale [27]. Wakefield et al ont récemment émis l'hypothèse d'un effet tératogène chez la souris lorsque la supplémentation en oméga 3 est réalisée pendant la période d'embryogenèse [28].…”
Section: Supplémentation En Omégas 3 Et 6 Chez L'animalunclassified